INTELLIGENT THERMAL INSULATION SYSTEMS WITH BUILT-IN MEANS OF REMOTE MONITORING OF HEAT TRANSFER PARAMETERS - Maksymenko, Vadym (European Journal of Interdisciplinary Issues, 2025)
Modern construction faces the challenge of increasing the energy efficiency of buildings by improving thermal insulation and reducing heat loss. Intelligent thermal insulation systems with built-in IoT solutions offer a new approach to controlling and optimizing heat transfer. This article considers the problem of the inefficiency of traditional insulation materials without monitoring. The purpose of the study is to analyze current technologies for remote monitoring of thermal parameters of building envelopes. The introduction substantiates the relevance of the topic, gives the share of buildings in global energy consumption and the need for smart insulation solutions. The state of development of IoT technologies in the field of thermal insulation is reviewed: from wireless sensor networks for tracking the impact of weather conditions to adaptive "smart" insulation materials with variable thermal conductivity. The main approaches and methods of monitoring heat transfer are described – the use of temperature sensors, hygrometers, heat fluxes and infrared control – using the example of several implemented systems. The results show the effectiveness of implementing IoT monitoring: high-frequency temperature control allows detecting thermal losses in real time and reducing energy consumption. The discussion focuses on practical aspects of application, comparing the obtained data with literary sources and Petrukha’s research on innovations in the construction industry. The conclusions summarize that the implementation of intelligent thermal insulation systems with remote monitoring increases the energy efficiency of buildings and contributes to sustainable development, while requiring consideration of cybersecurity and standardization for mass application.